Model Laboratorium Gerusan Lokal Pada Pilar Jembatan Tipe Cylinder Grouped Dengan Pengaman Pilar Tipe Tirai Pada Sungai Berbelok - Michael Chrisyie Daniel Bintang; Mudjiatko Mudjiatko; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Cylinder grouped pillars on meander experienced hydrodynamic and helicoidal force. Laboratory model with 7 testing variations wich are the test withouth pillars (Fr2Tp), 3 variations without curtains (Fr1P, Fr2P, Fr3P) dan 3 variations using curtains (Fr1Pp, Fr2Pp, Fr3Pp) are used to identify the phenomenon of local scouring of grouped cylinder type pillar with curtain protector on meander. The materials used in this research are Kampar River’s sand passing no.10 shieve with Gs value of 2,66 and grain size of d35 = 0,247 mm; d50 = 0,298 mm; dan d65 = 0,352 mm as well as flume with meander index of 1,009. Shield graphic of subcritical flow with characteristic froude numbers 0,4249; 0,6460; and 0,6981 and reynolds numbers Fr1, Fr2, Fr3 wich are 1658,416 (transition), 3081,683 (turbulence) and 4381,188 (turbulence) showed that the grain moved. The equilibrium of scouring occured on 75th minutes for Fr1 and Fr2, and 150th minutes for Fr3. The bigger of froude number showed helicoidal force that occured was smaller, and the grain size wich is transported was also bigger. The result of this research showed that the curtains can reduce local scouring on Fr1, Fr2, and Fr3 at about 53,33 %, 45,55%, and 60,00% respectively.Keyword : Local Scouring, Cylinder Grouped Pillars, Curtain Protector, Depth Ratio.